Assessment of the fishery and stock of striped bonito, Sarda orientalis (Temminck and Schlegel, 1844) along Kerala coast with a general description of its fishery from Indian coast - Sivadas, M (Indian Journal of Fisheries, 2012)
The striped bonito, Sarda orientalis is found to form a seasonal fishery all along the coasts of its occurrence except in Kerala where it is fished almost throughout the year. During the period 2006-2010, of the all India annual average catch of 849 t, Kerala contributed the maximum of 65.6% followed by Andaman and Nicobar (23.4%) with the rest being accounted for by Gujarat (6.6%), Tamil Nadu (2.3%), Andhra Pradesh (1.4%), Maharashtra (0.6%) and Karnataka (0.2%). From West Bengal and Odisha, no landing of the species has been reported. Size ranged from 16 to 68 cm. Mature fishes dominated in June and July. Size at first maturity was 42 cm FL. They are carnivorous fishes with crustaceans and cephalopods constituting the chief food items. Length-weight relationship was W = 0.00869 L 3.1 (n =134, r2 = 0.96). The von Bertalanffy growth equation was: Lt = 74.75 [1 - e – 0.68 (t + 0)]. The prediction analysis based on Kerala landing show that the current exploitation is well below the MSY level indicating scope for increasing the effort to exploit the resource.